The effects of central aromatic amino acid DOPA decarboxylase inhibition on the motor actions of L-DOPA and dopamine agonists in MPTP-treated primates - Treseder, Sarah A (2000)
1. Endogenous L-DOPA may act as a neuromodulator contributing to the production of motor activity. We now investigate the effects of the centrally acting aromatic amino acid dopa decarboxylase (AADC) inhibitor NSD-1015 (3-hydroxybenzyl hydrazine) on the motor actions of L-DOPA and dopamine agonist drugs in MPTP treated common marmosets. 2. Pretreatment with NSD-1015 (10–50 mg kg(−1); i.p.) worsened baseline motor deficits in MPTP-treated common marmosets. Similarly, it abolished L-DOPA (5–18 mg kg(−1) s.c.) induced locomotor activity and reversal of disability. NSD-1015 pretreatment inhibited dopamine formation and elevated L-DOPA levels in plasma. 3. The increase in locomotor activity and improvement in disability produced by the administration of the D-1 agonist A-86929 (0.03–0.04 mg kg(−1) s.c.) or the D-2 agonist quinpirole (0.05–0.3 mg kg(−1) i.p.) was abolished by NSD-1015 (25 mg kg(−1) i.p.) pretreatment. While the effects of a low dose combination of A-86929 (0.04 mg kg(−1) s.c.) and quinpirole (0.05 mg kg(−1) i.p.) were inhibited by NSD-1015 (25 mg kg(−1) i.p.), there was little effect on the action of a high dose combination of these drugs (0.08 mg kg(−1) A-86929 and 0.1 mg kg(−1) quinpirole). 4. Following central AADC inhibition with NSD-1015 (25 mg kg(−1) i.p.), locomotor behaviour induced by administration of high dose combinations of A-86929 (0.08 mg kg(−1) s.c.) and quinpirole (0.1 mg kg(−1) i.p.) was unaffected by L-DOPA (5 mg kg(−1) s.c.) pretreatment. 5. These results do not support a role for endogenous L-DOPA in spontaneous or drug induced locomotor activity. Rather, they strengthen the argument for the importance of endogenous dopaminergic tone in the motor actions of dopamine agonists.